Grammatical Errors in Arabic Composition Writing among Students of an Intensive Arabic Language Program - Hasla, Adinda Muhariani Permata; Aziz, Abdul; Ifawati, Nur Ila (Abjadia : International Journal of Education, 2025)
This study identifies grammatical errors in Arabic composition writing among students enrolled in an intensive Arabic language program and explores the factors contributing to these errors. Using a qualitative descriptive method, data were collected through student writing samples, interviews, and classroom observations. Findings reveal six major categories of grammatical errors: expression errors (i‘rāb), syntax (tarkīb), word position, nouns and pronouns, gender, and addition or omission of words. Contributing factors include internal aspects such as limited grammar understanding and insufficient practice, as well as external influences like first language interference and inadequate learning environments. The study concludes that addressing these factors through innovative teaching methods and improved resources can enhance Arabic language learning outcomes.